Development of functional materials with specific activities for degradation of toxins. (April 2019) - Efremenko, E; Ahundov, R; Aslanli, A; Lyagin, I; Senko, O; Maslova, O; Stepanov, N
Abstract: It was shown that it is possible to use different samples of hexahistidine-containing organophosphate hydrolase (His6 -OPH)-based enzyme preparations, including those obtained in the frame of functionalized materials, for the successful detoxification of organophosphorus compound such as Paraoxon and different mycotoxins (Zearalenone, Patulin, Sterigmatocystin) in their present in contaminated agricultural commodities. For the first time it was demonstrated that different toxins (xenobiotics and toxic compounds naturally produced by microscopic fungus) can be hydrolysed by the same enzyme and various biocatalysts prepared on the base of it use.